Market competition and lower tier incentives - Bernd Theilen (Center for Economic Studies and ifo Institute (CESifo), 2008)
The relationship between competition and performance-related pay has been analyzed in single-principal-single-agent models. While this approach yields good predictions for managerial pay schemes, the predictions fail to apply for employees at lower tiers of a firm's hierarchy. In this paper, a principal-multi-agent model of incentive pay is developed which makes it possible to analyze the effect of changes in the competitiveness of markets on lower tier incentive payment schemes. The results explain why the payment schemes of agents located at low and mid tiers are less sensitive to changes in competition when aggregated firm data is used.
Keywords: D82; J21; L13; L22; 330; Cournot competition; contract delegation; moral hazard; entry; market size; wage cost; Leistungsorientierte Vergütung; Mittleres Management; Agency Theory; Wettbewerb; Marktstruktur; Theorie